Silence, Silencing, and (In)Visibility: The Geopolitics of Tehran's Silent Protests. (2017) - Ranjbar, A. Marie
Abstract : This article examines the use of silent protests to resist state denial and appropriation of activist narratives. Drawing from feminist literary studies, I conceptualize silence as a pluralistic, multifaceted, and multi‐sited force. Through an analysis of several modalities of silence employed during Iran's 2009 election protests, I explore tensions between acts of silencing and silence as an act of dissent. I argue that silent protest is both an effect of—and resistance against—geopolitical conditions that subject Iranian citizens to state silencing. In this article, I examine: (i) the geopolitical conditions that enabled the silencing of Iranian citizens; (ii) meanings and interpretations of silent protests within Iran and internationally; (iii) the relationship among embodiment, scale, and visibility of Iranian protesters. I conclude with thoughts on reading silences across borders, while questioning the efficacy of silent protests in places considered geostrategically insignificant to the international community.